Well grounded: Indigenous Peoples' knowledge, ethnobiology and sustainability. Issue 3 (23rd March 2022) - Turner, Nancy J.; Cuerrier, Alain; Joseph, Leigh
Abstract: The biological knowledge and associated values and beliefs of Indigenous and other long‐resident Peoples are often overlooked and underrepresented in governance, planning and decision‐making at local, regional, national and international levels. Ethnobiology—the study of the dynamic relationships among peoples, biota and environments—is a field that places Indigenous Peoples' ecological knowledge and ways of knowing at the forefront of research interests, particularly in relation to the importance of biocultural diversity in sustaining the Earth's Ecosystems. In this paper, we examine the nature and significance of Indigenous Peoples' knowledge systems concerning environmental sustainability, as documented in collaborative ethnobiological research. We emphasize the diverse aspects of Indigenous knowledge in conservation, and the role played by ethnobiologists in respectfully highlighting this knowledge, and link these to the Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services Global Assessment's key levers and leverage points for enabling the transformative change required for achieving more sustainable lifeways. Drawing on diverse ways of knowing—respectfully, collaboratively, ethically and reciprocally—can help provide more detailed knowledge of local ecosystems, and guide all humans towards greater sustainability. From environmental monitoring, to building relationships with plants and the land, to ecological restoration, there are many lessons and ways in which the intersections between Indigenous knowledge and ethnobiology can inform and contribute to the future of humanity and other life on earth. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Abstract: Résumé Le savoir biologique ainsi que les valeurs et croyances des autochtones et autres communautés locales sont souvent ignorés et peu représentés dans le domaine de la gouvernance, de la planification et dans la prise de décision sur le plan local, régional, national et international. L'ethnobiologie, soit l'étude des liens dynamiques entre peuples, biotes et environnements, est un champ d'expertise qui inscrit le savoir écologique et l'approche à la connaissance des Peuples premiers au cœur des intérêts de la recherche, notamment en lien avec la diversité bioculturelle, qui importe pour ce qui a trait à la sauvegarde des écosystèmes de la Terre. Dans cet article, nous illustrons la nature et l'importance du savoir des Peuples autochtones dans le cadre de la durabilité environnementale tel qu'il est documenté par la recherche collaborative en ethnobiologie. Nous mettons l'emphase sur les divers aspects du savoir traditionnel autochtone en conservation ainsi que le rôle joué par les ethnobiologistes afin de les souligner tout en établissant des liens avec les leviers‐clés de la Plateforme intergouvernementale scientifique et politique sur la biodiversité et les services écosystémiques dans le but de permettre un changement transformatif requis pour un mode de vie plus durable. Prendre en compte ces savoirs de façon respectueuse, collaborative, éthique et réciproque peut aider à fournir une meilleure connaissance des écosystèmes locaux et guider tout être humain vers une plus grande durabilité environnementale. Partant des suivis environnementaux jusqu'à la création de relations avec les plantes et la terre tout en passant par la restauration écologique, il y a plusieurs leçons à tirer et plusieurs approches à découvrir au croisement du savoirs autochtones et de l'ethnobiologie qui peuvent contribuer à l'avenir de l'humanité et des autres formes de vie.